LANGKAH-LANGKAH KH AHMAD DAHLAN DALAM MEMODERNISASI ISLAM SEBELUM DAN PASCA MENDIRIKAN MUHAMMADIYAH 1890-1930 - Muhammad Nugraha Assydiqhi (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Kh Ahmad Dahlan is the son of a Khatib of the Great Mosque of Yogyakarta. KH Ahmad Dahlan has a desire to give his ideas in raising the Java people from the collapse of the colonization. KH Ahmad Dahlan formed the Muhammadiyah organization as a real form of the endeavour of his vision and mission to reform the Islamic world in Indonesia. To use the benefits of colonization as a weapon for Islamic people. As a pioneer of the Islamic Reform Movement KH Ahmad Dahlan laid the foundations of the way of management of organizations through congresses such as congresses and the ultimate purpose of this research is for nature This article has the purpose to review further about the thinking of KH Ahmed Dahlan influenced by some thinkers from the Middle East about the council of Islamic renewal in this regard review of the thought of Muhammad Abduh.and forms of Implementation and Actualization of these values in social life. This discussion contains two remarkable steps by KH Ahmad Dahlan in implementing the Modernization. The method used is the method of literature study which means that the data required in this research can be obtained from library sources or documents. The results of the research that was announced pointed to the role of Muhammadiyah in developing association and education for bumiputera.